Mathematical modeling and simulation of systems (MODS'2020) : selected papers of 15th International Scientific-practical Conference, MODS, 2020 June 29-July 01, Chernihiv, Ukraine /: selected papers of 15th International Scientific-practical Conference, MODS, 2020 June 29-July 01, Chernihiv, Ukraine. (2020) - Unknown
No abstract available